Inhibitory activities of propolis, nisin, melittin and essential oil compounds on Paenibacillus alvei and Bacillus subtilis - Sani, Alessandra Aguirra [UNESP]; Pereira, Ana Flávia Marques [UNESP]; Furlanetto, Alessandra [UNESP]; de Sousa, Débora Silva Marques [UNESP]; Zapata, Tatiane Baptista [UNESP]; Rall, Vera Lucia Mores [UNESP]; Júnior, Ary Fernandes [UNESP] (FapUNIFESP (SciELO), 2022)
Background: Natural products represent important sources of antimicrobial compounds. Propolis and compounds from essential oils comprise good examples of such substances because of their inhibitory effects on bacterial spores, including bee pathogens. Methods: Ethanol extracts of propolis (EEP) from Apis mellifera were prepared using different methods: double ultrasonication, double maceration and maceration associated with ultrasonication. Together with the antimicrobial peptides nisin and melittin, and compounds present in the essential oils of clove (Syzygium aromaticum) and cinnamon (Cinnamomum zeylanicum), assays were carried out on one Bacillus subtilis isolate and Paenibacillus alvei (ATCC 6344) against vegetative and sporulated forms, using the resazurin microtiter assay. Synergism with all the antimicrobials in association with tetracycline was verified by the time-kill curve method. Potassium and phosphate efflux, release of proteins and nucleic acids were investigated. Results: EEPs showed the same MIC, 156.25 µg/mL against B. subtilis and 78.12 µg/mL against P. alvei. The peptides showed better activities against B. subtilis (MIC of 12 µg/ mL for melittin and 37.50 µg/mL for nisin). Antimicrobials showed similar inhibitory effects, but cinnamaldehyde (39.06 µg/mL) showed the best action against P. alvei. Melittin and nisin showed the greatest capacity to reduce spores, regarding B. subtilis there was a 100% reduction at 6.25 and 0.78 µg/mL, respectively. Concerning P. alvei, the reduction was 93 and 98% at concentrations of 80 µg/mL of melittin and 15 µg/ mL of nisin. EEPs showed the highest effects on the protein release against B. subtilis and P. alvei. Nucleic acid release, phosphate and potassium efflux assays indicated bacterial cell membrane damage. Synergism between antimicrobials and tetracycline was demonstrated against both bacteria. Conclusion: All antimicrobials tested showed antibacterial activities against vegetative and sporulated forms of P. alvei and B. subtilis, especially nisin and melittin. Synergism with tetracycline and damage on bacterial cell membrane also occurred.
Keywords: Apis mellifera; Cinnamaldehyde; Eugenol; Melittin; Nisin; Sporicidal activity; Synergism; Tetracycline